Higher Education in the Time of Trump and Beyond: Resistance and Critique. (March 2023) - Spooner, Marc
The current Qualitative Inquiry partial special issue titled "Higher Education in the Time of Trump and Beyond: Resistance and Critique" is based on a similarly themed plenary panel that was to take place at the International Congress of Qualitative Inquiry in 2020. Alas, like so many other events, it was canceled due to the COVID-19 pandemic.